Green Haywood Hackworth papers - Hackworth, Green Haywood, 1883-1973.
Correspondence, print and near-print publications, articles, and addresses. Chiefly printed matter relating to Hackworth's career as a legal advisor with the U.S. Dept. of State and as a judge with the International Court of Justice. Subjects include international law; U.S. treaty developments; treaty agreements between Canada and the United States; and the Yalta voting formula, the provisions for voting by members of the UN Security Council. Includes material pertaining to the United Nations; American Arbitration Association; American Society of International Law; Americans United for World Organization; Panel on the Future of the International Court of Justice, American Arbitration Association; Teheran Conference, 1943; Conversations on International Organization, Washington, D.C, 1944, held at Dumbarton Oaks; United Nations Monetary and Financial Conference, Bretton Woods, N.H., 1944; United Nations Conference on International Organization, San Francisco, Calif., 1945; and the Yalta Conference, 1945. Correspondents include John C. Bruel, James F. Byrnes, Armand Chankalian, Hugh Baker Cox, Willis H. Crosswhite, John Sloan Dickey, Hardy Cross Dillard, William O. Douglas, Michael Francis Doyle, Angier Biddle Duke, Charles Fahy, Jean Garnier-Coignet, Stanley Kuhl Hornbeck, Manley O. Hudson, Cordell Hull, Philip C. Jessup, Arthur Larson, Howard S. Levie, G. Bernard Noble, Howard T. Oliver, Herman Phleger, Charles S. Rhyne, Durward V. Sandifer, and Edward R. Stettinius, Jr.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Jurist and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bruel, John C. -- Correspondence; Byrnes, James F. -- 1882-1972 -- Correspondence; Chankalian, Armand, -- 1903-1970 -- Correspondence; Cox, Hugh Baker, -- 1905-1973 -- Correspondence; Crosswhite, Willis H. -- Correspondence; Dickey, John Sloan, -- 1907-1991 -- Correspondence; Dillard, Hardy Cross, -- 1902-1982 -- Correspondence; Douglas, William O. -- 1898-1980 -- Correspondence; Doyle, Michael Francis, -- 1875-1960 -- Correspondence; Duke, Angier Biddle, -- 1915-1995 -- Correspondence; Fahy, Charles, -- 1892-1979 -- Correspondence; Garnier-Coignet, Jean -- Correspondence; Hornbeck, Stanley Kuhl, -- 1883-1966 -- Correspondence; Hudson, Manley O. -- 1886-1960 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Jessup, Philip C. -- 1897-1986 -- Correspondence; Larson, Arthur, -- Correspondence; Levie, Howard S., -- 1907- -- Correspondence; Noble, George Bernard, -- 1892-1972 -- Correspondence; Oliver, Howard T. -- Correspondence; Phleger, Herman, -- 1890-1984 -- Correspondence; Rhyne, Charles S., -- 1912-2003 -- Correspondence; Sandifer, Durward V. -- 1900-1981 -- Correspondence; Stettinius, Edward R. -- 1900-1949 -- Correspondence; United States. -- Department of State; American Arbitration Association; American Society of International Law; American Society of International Law. -- Panel on the Future of the International Court of Justice; Americans United for World Organization; International Court of Justice; United Nations; United Nations. -- Security Council; International agencies; International law; International law -- Congresses; International relations; Treaties; World War, 1939-1945.; Canada -- Foreign relations -- United States; United States -- Foreign relations -- Canada; United States -- Foreign relations; Jurists; Lawyers